Schweikart & Allen, A Patriot’s History Of The United States - From Columbus’ Great Discovery To The War On Terror - Dalton, C. David (Teaching History: A Journal of Methods, 2005)
Many college history professors find choosing a survey text an annual exercise in frustration- too much of this or too little of that to suit personal taste. When a new book comes onto the market, there is automatic interest in it. This text will be no exception, but for a very different reason.